MiR-155-5p positively regulates CCL17-induced colon cancer cell migration by targeting RhoA - Al-Haidari, Amr A. (Oncotarget, 2017)
Colorectal cancer is the second most common cause of cancer-related death, which is due to migration of tumor cells to distant sites of metastasis. Accumulating data indicate that mciroRNAs play an important role in several aspects of colon cancer cell biology. Herein, we examined the role of miR-155-5p in colon cancer cell migration induced by the CCL17-CCR4 axis in HT-29 colon cancer cells. We found that miR-155-5p knockdown in serum starved colon cancer cells decreased CCL17-induced cell chemotaxis. Moreover, knocking down miR-155-5p markedly decreased CCL17-provoked activation of RhoA in colon cancer cells. Bioinformatics analysis predicted two putative binding sites in the AU-rich element at the 3′-UTR of RhoA mRNA. MiR-155-5p binding to RhoA mRNA was verified using a target site blocker and functionally validated by RNA immunoprecipitation assays, showing that miR-155-5p-dependent regulation of RhoA mRNA is mediated by AU-rich elements present in the 3′-UTR region. Taken together, these results show that miR-155-5p positively regulates RhoA mRNA levels and translation as well as cell migration in serum starved colon cancer cells and indicate that targeting miR-155-5p might be a useful strategy to antagonize colon cancer metastasis.